2007
DOI: 10.1111/j.1473-6861.2007.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of an interprofessional education initiative for students in the health professions

Abstract: This paper reports the results of a 2‐year pilot study that involved 136 students from various health professions in 13 interprofessional education projects in north‐western Ontario, Canada. The educational model was based on principles of problem‐based, self‐directed, small group learning and combined a clinical placement with a series of interprofessional tutorials and other shared learning experiences. Project evaluation entailed the use of both quantitative and qualitative outcome measures. Student ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Effi cacy was understood to include perceptual changes about other professionals, improvements in communication, and ideas and strategies about teamwork (Ateah et al, 2011;Bilodeau et al, 2010;Cooper et al, 2009;Fortugno et al, 2013;Joyal et al, 2015;Meff e et al, 2012;Paul et al, 2014;Salvatori et al, 2007;Sommerfeldt et al, 2011;Vanderzalm et al, 2013). These fi ndings are consistent with several systematic reviews (Hammick, Freeth, Koppel, Reeves, & Barr, 2007;Lapkin, Levett-Jones, & Gilligan, 2013;Reeves et al, 2010;Reeves et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Effi cacy was understood to include perceptual changes about other professionals, improvements in communication, and ideas and strategies about teamwork (Ateah et al, 2011;Bilodeau et al, 2010;Cooper et al, 2009;Fortugno et al, 2013;Joyal et al, 2015;Meff e et al, 2012;Paul et al, 2014;Salvatori et al, 2007;Sommerfeldt et al, 2011;Vanderzalm et al, 2013). These fi ndings are consistent with several systematic reviews (Hammick, Freeth, Koppel, Reeves, & Barr, 2007;Lapkin, Levett-Jones, & Gilligan, 2013;Reeves et al, 2010;Reeves et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
“…Benefi ts of the interprofessional learning process have also been identifi ed. Several studies of IPE in Canadian nursing programs occurring prior to 2012 found similar results (Ateah et al, 2011;Basran et al, 2012;Bilodeau et al, 2010;Cooper, Macmillan, Beck, & Paterson, 2009;Graybeal, Long, Scalise-Smith, & Zeibig, 2010;Dobson et al, 2009;Meff e, Moravac, & Espin, 2012;Salvatori, Berry, & Eva, 2007;Sommerfeldt, Barton, Stayko, Patterson, & Pimlott, 2011). …”
Section: Ipe and Nursing Curricula Since 2012supporting
confidence: 58%
“…In fact, only the mean score of competency and authority components in professors who had some interprofessional education experience was higher than that of other professors. (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicate that IPE maximizes opportunities for students to learn in small groups in safe pedagogical environments (Dando, D'Avray, Colman, Hoy, & Todd, 2012;Mellor, Cottrell, & Moran, 2013;Salvatori, Berry, & Eva, 2007;Shiyanbola & Lammers, 2012;Shiyanbola, Randall, Lammers, Hegge, & Anderson, 2014;Solomon et al, 2010). IPE develops the trusting relations necessary to build collaborative practice and support students' and faculty's socialization to different philosophies of teaching and learning.…”
Section: Benefits Of Interprofessional Health Educationmentioning
confidence: 99%